Case report: 17α− hydroxylase deficiency due to a hotspot variant and a novel compound heterozygous variant in the CYP17A1 gene of five Chinese patients - Li, Jinying; Zhang, Qiang; Chen, Jing; Fu, Xingjiao; Yang, Jingpin; Liu, Lijun (Frontiers in Pediatrics, 2022)
17α-Hydroxylase deficiency (17OHD) is a rare form of congenital adrenal hyperplasia caused by mutations in the CYP17A1 gene. It is characterized by impaired adrenal and gonad steroid biosynthesis. Affected patients present with hypertension, hypokalemia, and disorders of sexual development. Here, we describe the genotypes and phenotypes of five patients from three families with this rare disease. Most patients had the hotspot variant, c.985_987delTACinsAA, in CYP17A1, which may be caused by a founder effect. However, the patients in our study were younger than the typical age of onset of 17OHD, and there was a pair of twins with the karyotypes 46, XX and 46, XY, but they both had a female phenotype. Meanwhile, we identified a novel compound heterozygous variant, c.1243+6T>G (p.Y329fs/splicing) in the CYP17A1 gene.